2000
DOI: 10.1128/jvi.74.10.4523-4529.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polyomavirus (Goose Hemorrhagic Polyomavirus) Is the Agent of Hemorrhagic Nephritis Enteritis of Geese

Abstract: We have identified the etiological agent of hemorrhagic nephritis enteritis of geese (HNEG), a fatal disease of European geese. HNEG has been recognized in almost all goose breeding areas, with an epizootic pattern, and up to now, the infectious agent has remained unknown. In order to identify the causative agent, infected tissues from HNEG-affected geese were inoculated to 1-day-old goslings, which then developed clinical signs typical of HNEG. Tissue homogenates from these birds were subjected to Freon extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
71
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 17 publications
2
71
0
Order By: Relevance
“…All avian polyomaviruses have an additional ORF located upstream of the VP2-encoding region, which in the case of GHPV encodes protein homologous to VP4 (designated as product of ORV-X) (10). The phylogenetic analysis carried out on the basis of the VP1 gene sequence confirmed that this virus is significantly divergent from other polyomaviruses and represents a distinct virus species in the Polyomavirus genus (8).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…All avian polyomaviruses have an additional ORF located upstream of the VP2-encoding region, which in the case of GHPV encodes protein homologous to VP4 (designated as product of ORV-X) (10). The phylogenetic analysis carried out on the basis of the VP1 gene sequence confirmed that this virus is significantly divergent from other polyomaviruses and represents a distinct virus species in the Polyomavirus genus (8).…”
Section: Introductionmentioning
confidence: 84%
“…High replication levels of GHPV in these birds have suggested that ducks may be a subclinical reservoir of the virus (17). The occurrence of the GHPV infection in other avian species seems to be very likely, because subclinical infections have been reported in migrating wild geese (8).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations